2008
DOI: 10.1063/1.3009298
|View full text |Cite
|
Sign up to set email alerts
|

Axisymmetric bubble collapse in a quiescent liquid pool. II. Experimental study

Abstract: We present an experimental study of the detachment of a gas bubble growing quasistatically at constant flow rate conditions from a vertical nozzle placed at the bottom of a quiescent pool of water. In particular, we focus on the dynamics of the necking process and on its dependence on both the Bond and Weber numbers, respectively, defined as Bo= ga 2 / , and We Q = Q 2 / ͑ 2 a 3 ͒. Here, a, , , g, and Q are the inner radius of the nozzle, the liquid density, the gas-liquid surface tension, the gravitational ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 18 publications
6
51
0
Order By: Relevance
“…Manasseh et al (1998) and Bolanos-Jiménez et al (2008) experimentally showed that this process also creates high speed jets. Indeed, as the bubble grows in size, the neck becomes more and more elongated and, eventually, surface tension triggers the pinch-off of the bubble, leading to the formation of two fast and small jets as illustrated in figure 3.…”
Section: Bubble Pinch-off From An Underwater Nozzlementioning
confidence: 99%
See 2 more Smart Citations
“…Manasseh et al (1998) and Bolanos-Jiménez et al (2008) experimentally showed that this process also creates high speed jets. Indeed, as the bubble grows in size, the neck becomes more and more elongated and, eventually, surface tension triggers the pinch-off of the bubble, leading to the formation of two fast and small jets as illustrated in figure 3.…”
Section: Bubble Pinch-off From An Underwater Nozzlementioning
confidence: 99%
“…For the quasi-static injection conditions considered here, the relevant dimensionless parameter characterizing this physical situation is the Bond number Bo = ρR 2 N g/σ [Longuet-Higgins et al (1991); Bolanos-Jiménez et al (2008)], which in the case presented here equals 2.1. More details of our simulation method are given in Oguz & Prosperetti (1993); Gekle et al (2009c).…”
Section: Bubble Pinch-off From An Underwater Nozzlementioning
confidence: 99%
See 1 more Smart Citation
“…In all these cases jetting seems thus to be accomplished by a mechanism different from the one in this Letter. In the case of drop impact [15,16] or gas injection through a needle [3,17], however, the formation of a cavity and its subsequent inertial collapse can sometimes be observed and the present mechanism might be of relevance.Our experimental setup consists of a circular disc with radius R 0 that is pulled through a water surface with velocity V 0 as described in [4]. The velocity V 0 is kept constant throughout the whole process.…”
mentioning
confidence: 99%
“…In all these cases jetting seems thus to be accomplished by a mechanism different from the one in this Letter. In the case of drop impact [15,16] or gas injection through a needle [3,17], however, the formation of a cavity and its subsequent inertial collapse can sometimes be observed and the present mechanism might be of relevance.…”
mentioning
confidence: 99%